Adjacent Segment Disease After Anterior Cervical Discectomy and Fusion in a Large Series. Issue 2 (21st October 2013) - Bydon, Mohamad; Xu, Risheng; Macki, Mohamed; De la Garza-Ramos, Rafael; Sciubba, Daniel M.; Wolinsky, Jean-Paul; Witham, Timothy F.; Gokaslan, Ziya L.; Bydon, Ali
Abstract: BACKGROUND: Adjacent segment disease (ASD) development is known to occur after anterior cervical discectomy and fusion (ACDF). OBJECTIVE: To study the relationship between index ACDF levels and the location of ASD development (above/below), as well as the effect of fusion length on ASD development. METHODS: We report 888 patients who underwent ACDF for cervical spondylosis over a twenty-year period at a single institution. Of these patients, 108 had re-do surgery due to symptomatic ASD. Patients were followed for an average of 92.4 ± 52.6 months after the index ACDF. RESULTS: In agreement with previous ACDF case series, we found the highest rates of cervical spinal degenerative disease requiring surgery at C5/C6, followed by C6/C7. Interestingly, neither the inherent location of index ACDF nor the length of instrumented arthrodesis appeared to correlate with the propensity to develop ASD. However, patients were more likely to develop ASD above the index level of fusion. This was true even for patients undergoing a second revision surgery due to recurrent ASD. Importantly, our data are consistent with existing in vitro biomechanical data in cadaveric spines. CONCLUSION: We describe in detail the location and length of arthrodesis for index ACDFs, as well as first and second revision fusion surgeries in one of the largest Western cohorts in the literature. Our findings support the theory that iatrogenically introduced stress and instability at adjacent spinal segments contribute to the pathogenesis of ASD.